EPO treatment does not alter acute serum profiles of GFAP and S100B after TBI: A brief report on the Australian EPO-TBI clinical trial. (June 2020) - Hellewell, Sarah C.; Conquest, Alison; Little, Lorraine; Vallance, Shirley; Board, Jasmin; Bellomo, Rinaldo; Cooper, David J.; Morganti-Kossmann, Maria Cristina
Highlights: GFAP and S100B are highest within 24h of moderate-severe traumatic brain injury. S100B discriminates favorable vs unfavourable 6-month outcomes as assessed by GOS-E. EPO does not affect the concentration of GFAP or S100B after moderate-severe TBI. Abstract: Purpose: To determine the diagnostic and prognostic value of glial fibrillary acidic protein (GFAP) and S100B after traumatic brain injury (TBI) in an Erythropoietin (EPO) clinical trial and examine whether EPO therapy reduces biomarker concentrations. Materials and Methods: Forty-four patients with moderate-to-severe TBI were enrolled to a sub-study of the EPO-TBI trial. Patients were randomized to either Epoetin alfa 40, 000 IU or 1 ml sodium chloride 0.9 as subcutaneous injection within 24 h of TBI. Results: GFAP and S100B were measured in serum by ELISA from D0 (within 24 h of injury, prior to EPO/vehicle administration) to D5. Biomarker concentrations were compared between injury severities, diffuse vs. focal TBI, 6-month outcome scores (GOS-E) and EPO or placebo treatments. At D0 GFAP was significantly higher than S100B (951 pg/mL vs. 476 pg/mL, p = 0.018). ROC analysis of S100B at 1D post-injury distinguished favorable vs. unfavorable outcomes (area under the curve = 0.73; p = 0.01). EPO did not reduce concentration of either biomarker. Conclusions: Elevated serum concentrations of GFAP and S100B after TBI reflect a robust, acute glial response to injury. Consistent with lack of improved outcome in TBI patients treated with EPO and prior findings on neuronal and axonal markers, glial biomarker concentrations and acute profiles were not affected by EPO.